Distribution and chemical structure characteristic of the fast thermal-cracking products of Buton oil sand bitumen by Py–GC/TOF–MS and a fluidized bed reactor. (1st March 2019) - Hao, Junhui; Zong, Peijie; Tian, Yuanyu; Zhang, Jinhong; Qiao, Yingyun
Highlights: The fast thermal-cracking experiments were performed by Py-GC/TOF-MS and a fluidized bed reactor. Five styles of compounds were contained in volatile products of OSB. Relative content distribution of volatile products with temperature/carbon number was discussed. Effect of temperature on yield and distribution of products for OSB was revealed. Chemical structures of liquid products remarkably changed compared to OSB. Abstract: In order to obtain a deep insight into the upgrade of oil sand bitumen (OSB), the composition, distribution and chemical structure of products obtained from the fast thermal cracking of the OSB were investigated via Py-GC/TOF-MS and a laboratory-scale fluidized bed reactor. A detail composition information of fast thermal-cracking products of the OSB was determined by Py-GC/TOF-MS, which mainly contained alkenes (1-alkenes, iso-alkenes and cycloalkenes), alkanes (n-alkanes, iso-alkanes and cycloalkanes), diolefins, aromatics and sulfur-containing compounds. The distribution of fast thermal-cracking products varied under different temperature. Alkenes were the uppermost style in volatile products at the temperature ranging from 500 °C to 700 °C, whereas with the temperature further rising to 800 °C, aromatics products became predominant and were mainly generated from the deep cleavage of alkyl substituent groups and the secondary reactions to form aromatics. Moreover, the relative content and carbon number distribution of volatile products along with various temperature were summarized. The thermal cracking experiments of the OSB over silica sand in a laboratory-scale fluidized bed reactor showed that the gas products had a remarkable increase in yield as the temperature increase, which was connected with the increase in methane and ethylene of dry gas as well as propylene and butenes of LPG. The coke yield also exhibited an increase tendency with the enhancement of temperature, while this variation was slighter in comparison to that of gases. Conversely, the yield of liquid products gradually decreased with the temperature, which was closely related to the significant decrease of VGO and heavy oil fractions due to the coke formation of polyaromatics and the intensive rupture of alkyl side chains. Nevertheless, the light oil fraction (diesel and gasoline) displayed the different variation along with the temperature, which increased firstly and then decreased as a result of the decomposition of heavy fractions and secondary cracking of light oil itself. Compared to the native OSB, there was a slight difference in functional group distribution for liquid products which was concerned with the formation of olefins, whereas the average structural parameters of the liquid products changed dramatically after the fast thermal cracking of the OSB. Furthermore, the effects of the reaction temperature on the chemical structures were significant due to the decomposition, condensation and secondary reactions proceeded during the fast thermal cracking process.